Labour Productivity Dynamics in Europe: Alternative Explanations for a Well Known Problem - Antonio Godinho Rodrigues (European Regional Science Association (ERSA), 2006)
The study of regional dynamics in employment productivity has been the basis for a large body of literature; the use in cross-section applications of the well known linear relationship between changes in productivity and Output growth first proposed in 1949 by P.J. Verdoorn has allowed greater insights into the dynamic nature of economic systems. Furthermore, it has been shown that a positive Verdoorn coefficient represents the existence of localized increasing returns, which contradicts Neoclassical orthodoxy. In this paper, a dynamic analysis of labour productivity in manufacturing is performed for a sample of 211 European Union regions. Three hypothesis are tested: first, following recent work by Bernard Fingleton (1999 & 2000), two components related to Growth Theory are added to the original Verdoorn relation, the productivity gap between each spatial unit and the leader in the first period and two proxies for human capital. Second, the importance of the Marshallian type externality as well as economies of urbanization is tested. These factors are calculated according to the weighted density of each variable at the NUTS3 level for each of the 211 NUTS2 regions, following the work of Ciccone and Hall (1996). Finally, and following the ideas presented in the seminal paper by Chinitz (1961), the importance of the industrial mix and the level of regional specialization/diversity is taken into account through the use of a spatially weighted specialization measure. Spatial Econometrics methods are used and alternative forms for the spatial weights matrix are tested, based on time distances calculated using a network model built with the existing road network. Legal speed limits permit an accurate calculation of distance between each node.
Keywords: 330